Answer:
The sentence in mathematical form is: [tex]5x+10 = x-6[/tex]
Step-by-step explanation:
The given statement can be converted into a mathematical equation step by step.
First of all, we have to suppose a variable for the number as we don't know the exact number.
So,
Let x be the number then
five times a number => 5x
The sum of 10 and five times a number => 5x+10
the difference of the number and 6 => x-6
Putting in equation form we get
[tex]5x+10 = x-6[/tex]
Hence,
The sentence in mathematical form is: [tex]5x+10 = x-6[/tex]